Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s12890-017-0475-6
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory mechanics in infants with severe bronchiolitis on controlled mechanical ventilation

Abstract: Background: Analysis of respiratory mechanics during mechanical ventilation (MV) is able to estimate resistive, elastic and inertial components of the working pressure of the respiratory system. Our aim was to discriminate the components of the working pressure of the respiratory system in infants on MV with severe bronchiolitis admitted to two PICU's. Methods: Infants younger than 1 year old with acute respiratory failure caused by severe bronchiolitis underwent neuromuscular blockade, tracheal intubation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 26 publications
2
24
0
1
Order By: Relevance
“…They observed reopening of the collapsed lung with addition of 5 cmH 2 O of PEEP for 5 min [ 14 ]. Kadini et al, in a small study of 8 anesthetized children (range between 2.5 and 6.5 years old), described that 5 cmH 2 O resulted in a significant increase of VT; thus, C RS improved [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed reopening of the collapsed lung with addition of 5 cmH 2 O of PEEP for 5 min [ 14 ]. Kadini et al, in a small study of 8 anesthetized children (range between 2.5 and 6.5 years old), described that 5 cmH 2 O resulted in a significant increase of VT; thus, C RS improved [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is little evidence to guide MV during general anesthesia in children [ 18 , 22 , 23 ]. MV parameters are primarily dependent on anesthesiologist preferences and on the characteristics of anesthesia machines [ 24 ]. Facing this scenario, many scientific societies have pointed as priority areas of research to the pathophysiology, respiratory mechanics and practice of MV in children for improving outcomes and reducing secondary long-term lung injury [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted on infants < 12 months of age affected by bronchiolitis and on MV confirmed that the elastic component is the strongest constituent of working pressure, thus describing bronchiolitis as a restrictive disease, beside the obstructive pattern. 17 These findings are of particular relevance, since they influence the ventilation parameters during MV of infected infants.…”
Section: Invasive Respiratory Supportmentioning
confidence: 95%
“… 14 15 All this implies a functional impairment of bronchioles, which may cause excessive work of breathing, hypoxia and hypercapnia, sometimes requiring invasive mechanical ventilation (IMV). 16 …”
Section: Introductionmentioning
confidence: 99%
“…14 15 All this implies a functional impairment of bronchioles, which may cause excessive work of breathing, hypoxia and hypercapnia, sometimes requiring invasive mechanical ventilation (IMV). 16 In 12 infants with viral bronchiolitis requiring intubation, Dargaville et al 14 observed an impaired functional activity of endogenous surfactant, which resolved after clinical healing of the disease. Subsequent studies reported alterations in both surfactant proteins and pulmonary surface tension, using the 'pulsating bubble surfactometer' method or the 'click test' in tracheal aspirates obtained from children with bronchiolitis.…”
mentioning
confidence: 99%